OPTIMALISASI DIGITALISASI UMKM MELALUI PENDAFTARAN GOOGLE MAPS DI DUSUN JEGONG, DESA JAMBANGAN, KECAMATAN DAMPIT, KABUPATEN MALANG - Arif Budijanto; Rahmatus Sania; Ana Maulidatul Qur'ania; Yohanes Rangga Mone; Elisabet Kahale; Christoforus Konstanstriyanus Haghe; Surya Mangngi; Dede Ayu Setiawati; Selvianti Mbaru; Oktavianus Daha Wole (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Jegong Hamlet, Jambangan Village, Dampit District, Malang Regency, have significant local economic potential, particularly in the tofu and tempeh production sector. However, most businesses have not yet integrated into digital platforms such as Google Maps. This condition has resulted in low business visibility and limited market access. This community service program aims to increase the visibility and competitiveness of MSMEs by assisting in registering business locations on Google Maps. The implementation method includes identification and data collection of MSMEs, technical planning, registration and optimization of digital business profiles, as well as monitoring and evaluation. The results show that of the 16 MSMEs recorded, 13 MSMEs successfully created Google Maps accounts, while 3 MSMEs had previously registered. Overall, this program has contributed to improving digital literacy, expanding market access, and strengthening the competitiveness of MSMEs in Jegong Hamlet.